Prognostic Impact of Histopathology in Patients with Advanced Stage Cervical Carcinoma Treated with Radiotherapy - Hossain, Nasrin; Perveen, Rahana; Mahmud, Mohammed Sharif; Hassan, Mohammed Kabirul (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: Cervical cancer is the fourth most common cancer in women worldwidev . Most patients in developing countries including Bangladesh present at advanced stage. Histopathological types of cervical cancer influence the treatment outcome when treated by radiation therapy. Objective: To determine the disease free survival (DFS) in different histopathological types in advanced stage cervical carcinoma treated with radiotherapy. Methods: A prospective cohort study was conducted in Gynaecological oncology outpatient department (GOPD) of National institute of Cancer Research & Hospital (NICRH), Dhaka for one year from September’2016 to July’2017. Advanced stage (IIB-IVB) cervical cancer who completed radiation therapy and histopathological type either squamous cell carcinoma or adenocarcinoma of cervix were included in this study. Results: The median follow-up time was 1.82 years; range was 8 to 24 months. Average disease free survival (DFS) was 1.53years in squamous cell carcinoma (SSC) and 1.51 years in adenocarcinoma (ADC). Local recurrences was higher in adenocarcinoma group (62.5%) than squamous cell carcinoma (30.5%) & the difference was statistically significant (p = 0.001). Loco-regional recurrence and distal recurrence were also higher in ADC than SSC but results were not statistically significant (p=.345, p=.795). In multivariate analysis it was shown that histopathological type and stage of disease were found to be independently significant prognostic factors for DFS, hazard ratio were 1.766 (p=.018) and 2.173 (p=.006). Conclusion: Adenocarcinoma was a poor prognostic factor for patients with locally advanced cervical carcinoma. Advanced stage of disease was also significant predictor for disease free survival. J Bangladesh Coll Phys Surg 2019; 37(4): 175-180